2019
DOI: 10.15405/epsbs.2019.03.02.25
|View full text |Cite
|
Sign up to set email alerts
|

Globalization Of Financial System And Its Synergetic Effect At Regional Level

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study conducted by the investment company Peter Trust JSC revealed that a significant part of domestic companies not only does not want to engage in risk management (hedging), but in most cases are not sufficiently informed. Russian companies avoid the use of derivative financial instruments in view of the extremely incompetent attitude to the topic of risk hedging, which is associated with the corporate governance system and the psychology of company employees (Bayguzina et al, 2019). The problem of the perception of derivatives by specialists of most companies rests on the complex nature of the emergence and existence of these assets.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by the investment company Peter Trust JSC revealed that a significant part of domestic companies not only does not want to engage in risk management (hedging), but in most cases are not sufficiently informed. Russian companies avoid the use of derivative financial instruments in view of the extremely incompetent attitude to the topic of risk hedging, which is associated with the corporate governance system and the psychology of company employees (Bayguzina et al, 2019). The problem of the perception of derivatives by specialists of most companies rests on the complex nature of the emergence and existence of these assets.…”
Section: Resultsmentioning
confidence: 99%